Dance Training Methods at Bangkit Sekar Budaya Cilacap Art Studio - Khakimah, Putri; Malarsih, Malarsih (Universitas Negeri Semarang, 2024)
Training is a teaching and learning activity that has the aim of improving a person's understanding, skills, and expertise in a particular field. This research aims to analyze the training methods applied and the factors that influence dance practice at Sanggar Bangkit Sekar Budaya (BSB). Training methods are closely related to training activities,therefore they are very important to use. This research uses descriptive qualitative methods. The research was conducted at Sanggar Bangkit Sekar Budaya Cilacap. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used are data reduction, presenting data, and drawing conclusions. The data validity techniques used are source triangulation and methodology triangulation. The results of this research show that several dance training methods are applied as follows, the methods used to convey theory are lectures, questions, and answers, while the methods used to improve skills in training are demonstrations, questions and answers, and drills. , assignments, peer tutoring, and outdoor study. Factors that influence dance training in studios consist of supporting factors, namely the instructor's family, parents, environment, students' physiological factors, desires, determination, talent, students' self-confidence, etc. Inhibiting factors include students not being serious, time conflicts, student fatigue, lack of discipline, progress not following the vision and mission, and location of the art studio.